Association of circulating omentin level and metabolic-associated fatty liver disease: a systematic review and meta-analysis - Zhang, Qin; Chen, Shuaihang; Ke, Yani; Li, Qicong; Shen, Chenglu; Ruan, Yuting; Wu, Kaihan; Hu, Jie; Liu, Shan (Frontiers in Endocrinology, 2023)
Abstract Background: Metabolic-associated fatty liver disease (MAFLD) is closely associated with omentin, a novel adipokine that plays a vital role in metabolic balance. The literature about the relationship between circulating omentin and MAFLD is conflicting. Therefore, this meta-analysis evaluated circulating omentin levels in patients with MAFLD compared with healthy controls to explore the role of omentin in MAFLD. Methods: The literature search was performed up to April 8, 2022, using PubMed, Cochrane Library, EMBASE, CNKI, Wanfang, CBM, Clinical Trials Database and Grey Literature Database. This meta-analysis pooled the statistics in Stata and presented the overall results using the standardized mean difference (SMD) and 95% confidence interval (CI). Results: Twelve studies with 1624 individuals (927 cases and 697 controls) were included, and all of them were case-control studies. In addition, ten of twelve included studies were conducted on Asian participants. Patients with MAFLD had significantly lower circulating omentin levels than healthy controls (SMD=-0.950 [-1.724, -0.177], P=0.016). Subgroup analysis and meta-regression demonstrated that fasting blood glucose (FBG) might be the source of heterogeneity and was inversely associated with omentin levels (coefficient=-0.538, P=0.009). No significant publication bias existed (P>0.05), and outcomes were robust in the sensitivity analysis. Conclusion: Lower circulating omentin levels were associated with MAFLD, and FBG might be the source of heterogeneity. Since Asian studies accounted for a significant portion of the meta-analysis, the conclusion might be more applicable to the Asian population. By investigating the relationship between omentin and MAFLD, this meta-analysis laid the foundation for the development of diagnostic biomarkers and treatment targets.